1994
DOI: 10.3109/08977199409010989
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Insulin-Like Growth Factor Binding Proteins (IGFBPs) 1 and 2 Induced in Vitamin C-Deficient or Fasted Guinea Pigs Inhibit IGF-I Action in Cultured Cells

Abstract: Collagen gene expression and proteoglycan synthesis are decreased in vitamin C-deficient guinea pigs losing weight and in fasted guinea pigs receiving ascorbate. Sera from such guinea pigs contain an insulin-like growth factor (IGF)-I-reversible inhibitor of collagen, proteoglycan and DNA synthesis and elevated levels of 29 and 35-kDa IGF binding proteins (IGFBPs). We now have identified the induced proteins as IGFBPs 1 and 2 and investigated their role as inhibitors. Guinea pig sera were treated with antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Some studies of humans also showed that high plasma levels or dietary intake of antioxidants is associated with increased bone mineral density [13][14][15]. In addition, vitamin C is a cofactor in collagen formation and hydroxylation of lysine and proline [16], which are important for bone maintenance [17]. This nutrient also stimulates in vitro osteoblast differentiation and alkaline phosphatase activity, thereby contributing to bone formation [18,19].…”
Section: Introductionmentioning
confidence: 93%
“…Some studies of humans also showed that high plasma levels or dietary intake of antioxidants is associated with increased bone mineral density [13][14][15]. In addition, vitamin C is a cofactor in collagen formation and hydroxylation of lysine and proline [16], which are important for bone maintenance [17]. This nutrient also stimulates in vitro osteoblast differentiation and alkaline phosphatase activity, thereby contributing to bone formation [18,19].…”
Section: Introductionmentioning
confidence: 93%
“…Peterkofsky et al (1991) reported elevated levels of the insulin like growth factor (IGF)-binding proteins (IGFBPs) in vitamin C deficient guinea pigs (this species, similarly to humans is unable to form endogenous AA). Moreover, when these IGFBPs were added to the cultured cells, they inhibited IGF-1-mediated growth (Peterkofsky et al, 1994). Notably, IGF-1 is a well known and potent mitogen for the undifferentiated muscle cells (Engert et al, 1996).…”
Section: Introductionmentioning
confidence: 98%
“…IGFBP-2 was found in the cytoplasmic fraction by Western immunoblot 31 in three separate subfractionations from the same cell preparation (these were denominated I to III: for sets I and II the cells were taken from spinner culture on day 2 and for set III they were removed on day 5, as described above and in the Fig. 3 legend).…”
Section: Igfbp-2 Localizationmentioning
confidence: 99%